Decentralised and Cooperative Aid Provision with Short-Term and Long-Term Aid - Strand, Jon (2012)
The authors analyze two donors providing long- and short-run aid to one receiving (poor) country, and who may give aid in coordinated or non-coordinated fashion. An elite controls receiver policy, and diverts resources away from a poor target group. When strategic moves are simultaneous, there is excessive wasteful short-run aid diversion, which could be made worse by donor cooperation. When donors move first, aid is lower, donor utility is higher, and donors should always cooperate. Investments, by the receiving country and due to long-term aid, is greater and the solution more efficient when investments are complements than when they are substitutes. The model characterizes donors that may be considered as "gullible", or as "skeptical". The former type gives generously but its aid is largely wasted; the latter gives less aid, but also wastes less.